1990
DOI: 10.1192/s0007125000291873
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Depression in Old Age Using Single-Photon Emission Computerised Tomography

Abstract: There is evidence to suggest that organic cerebral changes occur in elderly depressed patients. Quantitative studies of elderly depressed patients have demonstrated that they have reduced ‘radio-attenuation’ on computerised tomography (CT) scans and as a group resembled more closely a group of demented patients than normal controls (Jacoby et al, 1983). Many biochemical changes associated with ageing are similar to the pathophysiological abnormalities in depression and in dementia (Alexopoulos et al, 1988). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 26 publications
3
25
1
1
Order By: Relevance
“…The neuroanatomical and physiological correlates of major depression in late-life have been relatively well characterized (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Widespread reductions in glucose use and cerebral blood flow have been demonstrated in late-life MDD by using positron emission tomography (PET), Xenon 133 inhalation, and single photon emission-computed tomography (SPECT) (29,30,(39)(40)(41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroanatomical and physiological correlates of major depression in late-life have been relatively well characterized (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Widespread reductions in glucose use and cerebral blood flow have been demonstrated in late-life MDD by using positron emission tomography (PET), Xenon 133 inhalation, and single photon emission-computed tomography (SPECT) (29,30,(39)(40)(41).…”
mentioning
confidence: 99%
“…Widespread reductions in glucose use and cerebral blood flow have been demonstrated in late-life MDD by using positron emission tomography (PET), Xenon 133 inhalation, and single photon emission-computed tomography (SPECT) (29,30,(39)(40)(41). Glucose hypometabolism in MDD occurs in neocortical and subcortical regions (29).…”
mentioning
confidence: 99%
“…This correlation appears to be nonlinear; very weak in the mild stage of the dementia, and strong in severe cognitive defi cit. This tendency was confirmed by the separate analysis of correlation in the severe (MMSE between 0 and 15) 18 Robert/Migneco/Darcourt/Ricq/Aubin/ Bonhomme/Pringuey/Lapalus/Darcourt 99mTc-HMPAO Brain Uptake and Severity of Dementia The method of analysis we used differs from other studies [13][14][15][16][17], since the analysis uses anatomical stereo taxic data, allowing for localization of the precise anatom ical lobes (frontal, temporal, parietal and occipital) and to determine a functional temporoparietal region. In the majority of previous studies, ROIs were manually drawn making reference to a standard anatomical atlas [16,32,37], and used small areas: 16 pixels (4 X 4) [ 14], 81 pixels (9 X 9) [16], 9 pixels (3 X 3) [33].…”
Section: Discussionmentioning
confidence: 66%
“…99mTc-HMPAO (hexamethylpropylene amineoxyme) is the most recent brain perfusion tracer used in SPECT studies [10,11]. Geaney and Abou-Saleh [12] reviewed a large number of 99mTc-HMPAO AD studies in which a temporal and pari etal reduction of rCBF was found [13][14][15][16][17].…”
mentioning
confidence: 99%
“…She was administered approximately 550 MBq of 99Tc"HMPAO and was positioned beneath a large field-of-view gamma camera (Siemens ZLC Orbiter: 75 tube). The acquisition of tracer uptake data and its reconstruction, attenuation correction and normalization details are described elsewhere (Upadhyaya et al, 1990).…”
Section: Spet: Data Acquisition and Analysismentioning
confidence: 99%